Body composition and myokines in a cohort of patients with Becker muscular dystrophy. Issue 1 (27th May 2022) - Barp, Andrea; Carraro, Elena; Goggi, Giovanni; Lizio, Andrea; Zanolini, Alice; Messina, Carmelo; Perego, Silvia; Verdelli, Chiara; Lombardi, Giovanni; Sansone, Valeria Ada; Corbetta, Sabrina
Abstract: Introduction/Aims: Becker muscular dystrophy (BMD) is an X‐linked disease leading to muscle wasting and weakness. The decrease in lean body mass (LBM) in Duchenne muscular dystrophy, has shown correlation with loss of muscle function and bone density (BD). Myokines (including irisin) are hormones secreted by skeletal muscle that allow crosstalk between muscle and bone. The present study analyzed body composition and circulating myokine levels in a cohort of BMD patients; moreover, the association between dual energy X‐ray absorptiometry (DXA) parameters, functional motor assessments, and myokine levels was investigated. Methods: All patients underwent DXA, blood samples for myokine assays, and functional motor assessments. A group of healthy controls (HCs) was also included. Results: Thirty BMD patients, median age at evaluation 36.0 y [26.0–41.0], were included. Twenty‐nine patients underwent whole‐body DXA. Median value of total body Z‐score was −0.70. The prevalence of low skeletal muscle mass defined as appendicular skeletal muscle mass index (ASMMI) < 7.59 kg/m 2 was 83%. Irisin levels were significantly lower in BMD compared to HCs ( p  = .03). All DXA parameters showed significant correlation with the functional motor assessments, in particular the h 2 ‐standardized lean mass lower limb index ( p  = .0006); h 2 ‐standardized total fat mass showed negative correlations with North Star Ambulatory Assessment and 6 min walk test ( p  = .03). Discussion: DXA is a useful tool to evaluate body composition in BMD patients; the decrease in BD and LBM is associated with a reduction of motor function in BMD.